Brand positioning of Kota Bharu as Islamic city / Hasnina Hassan, Ghazali Ahmad and Roslizawati Che Aziz - Hassan, Hasnina; Ahmad, Ghazali; Che Aziz, Roslizawati (Faculty of Hotel and Management, Universiti Teknologi MARA, Selangor, Kampus Puncak Alam Campus, 2017)
Over the last 30 years, place marketing has become an increasingly mutual strategy for entrepreneurial cities, regions and countries seeking to gain advantage in a competitive environment. Competition between places is global. Kota Bharu is the state capital of Kelantan, on the east coast of Peninsular Malaysia and was rebranded by the state government from a cultural city into an Islamic city since 2005. Hence, the urban design of the city is in the track of creating a city which could be related to an Islamic identity. City branding is one of the most frequent forms of place marketing that requires the local authorities to place a great emphasis on the physical renewal of the cities. A research on brand positioning is needed to explore the city transformation throughout the branding process. This conceptual paper aims to explore the concept traditional and modern Islamic city, to understand the overall Kota Bharu Islamic city built environment, and outline the brand positioning of Islamic city concept through observation to the built environment and content analysis method focusing on series of guidelines report published by MPKB-BRI. The paper’s main objective is to highlight the city brand positioning by the local authority in building the city brand identity. The findings of Kota Bharu Islamic city brand positioning are explained through segmentation of three steps of city branding process in every five years initiated from the destination branding elements.